2003
DOI: 10.1111/1464-0597.00156
|View full text |Cite
|
Sign up to set email alerts
|

The Transparent Assessment Centre: The Effects of Revealing Dimensions to Candidates

Abstract: Quelles retombées peut avoir le fait de dévoiler aux participants les dimensions mesurées dans un centre d'évaluation ? Cette question est abordée dans deux études indépendantes qui font appel à des exercices individuels. Les résultats de la première étude n'indiquent aucune différence dans la validité de construction entre un groupe d'étudiants universitaires "transparent" ( N = 99) et un autre "non transparent" ( N = 50) ; ceci est contraire à ce qu'avaient trouvé Kleinmann & al. (1996) et Kleinmann (1997 av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 42 publications
5
27
0
1
Order By: Relevance
“…Given the lack of research on the influence of interview transparency on interviewees' performance and the mixed findings reported in the related literature on ACs (Kleinmann, 1997;Kleinmann et al, 1996;Kolk et al, 2003;Smith-Jentsch, 1996), our study's finding of increased performance in the transparent condition highlights the difference between high-and low-fidelity simulations. Although interviews are usually more practicable and cost-efficient than ACs and are widely accepted among hiring organizations, they represent only low-fidelity simulations in which actual behavior needs to be inferred from interviewees' answers without interviewees proving that they are truly capable of enacting the required behavior (Motowidlo et al, 1990).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Given the lack of research on the influence of interview transparency on interviewees' performance and the mixed findings reported in the related literature on ACs (Kleinmann, 1997;Kleinmann et al, 1996;Kolk et al, 2003;Smith-Jentsch, 1996), our study's finding of increased performance in the transparent condition highlights the difference between high-and low-fidelity simulations. Although interviews are usually more practicable and cost-efficient than ACs and are widely accepted among hiring organizations, they represent only low-fidelity simulations in which actual behavior needs to be inferred from interviewees' answers without interviewees proving that they are truly capable of enacting the required behavior (Motowidlo et al, 1990).…”
Section: Discussionmentioning
confidence: 55%
“…Transparency was manipulated in the same way as it had been done in earlier studies (Kleinmann, 1997;Kleinmann et al, 1996;Kolk et al, 2003). Participants in the transparent condition received an introduction and a handout with defini-tions of each dimension.…”
Section: Study 1 Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as past research has found that cognitive ability is correlated to candidates' ability to identify criteria (Kolk et al ; König et al, ; Melchers et al, ; Preckel & Schüpbach, ), the present research also offers an opportunity to further investigate reasons for this correlation. Specifically, we suggest that cognitive ability correlates with d′ but not with c .…”
Section: Theoretical Backgroundmentioning
confidence: 76%
“…It may seem radical to disclose to respondents what is being measured in a personality inventory but some research suggests that such disclosure may yield better validity. For instance, there was an article in Applied Psychology: International Review (Kolk, Born & van der Flier, 2003) that examined the impact of making assessment center dimensions available to applicants versus not making them available. They found some improvement in construct validity when the applicants knew the dimensions on which they were being tested.…”
mentioning
confidence: 99%